Enhancing Business Performance through Religiosity Leaderships Style among the Small and Medium Enterprises - Ezanee Mohamed Elias; Noorul Sadiqin Azbiya Yaacob; Siti Norezam Othman (International Journal of Supply Chain Management, 2018)
The objective of the study is to investigate the role of religiosity leaderships style among the top management of halal food and beverages products small and medium sizes manufacturers towards their business performance. Presently, leadership style is one of crucial elements for leaders or managers in the organization to provide business directions, implement strategic plans and motivate employees. Nowadays the importance of leadership not only be influenced by participative, transformational or laissez-faire but the guidance from the religiosity also be equally significant. Usually, leadership practices are influenced by individuals religious liaison and religiosity practices. In this study, it was intended to fill a gap where a few studies have been done so far on religiosity leadership at SMEs but not particularly in the manufacturing of halal FB products. Thus, the study proposes a theoretical framework in order to examine the effect of religiosity leaderships style towards the SMEs business performance which moderated by halal entrepreneurial orientation. A quantitative design with a simple random sampling and establishment by emails (online survey questionnaires) will be distributed to 370 SMEs in Malaysia. The data were analyzed by SPSS and Smart SEM-PLS. The finding of the study will indicate that the religiosity leaderships have mixed results. In this context, religiosity leaderships make a significant contribution to SMEs'in a way of increasing business performance at a certain market segmentation.